Review of Environmental, Economic and Energy Impact of Waste-To-Energy in Malaysia - DERAOH, AHMAD AL-SYUKRI; AZMI, MUHAMMAD AKMAL FARIS MAHADI; NORSHAMSURI, MUHAMMAD AIMAN TAHFIZ; BASKARAN, DENISH KUMAR; NUGRAHA, ANDHYKA TYAZ (Journal of Optimization System and Ergonomy Implementation, 2024)
The increase in the national human population, economic progress, and technological advancements have collectively resulted in a significant surge in the need for energy. However, the depletion of conventional resources and the crisis of global warming are impeding the government's ability to meet the requirements of its citizens. One potential solution to address the aforementioned issues involves the adoption of Waste-To-Energy (WTE) systems, which has the capability to convert various forms of trash into usable energy. In addition to serving as an alternative energy source, Waste-to-Energy (WTE) technology has the potential to alleviate the challenges associated with trash disposal within a given nation. Hence, the aim of this study is to critically examine the environmental, economy and energy consequences associated with Waste-to-Energy (WTE) practices within the nation. This article centers its attention on organic waste and biomass, including crop output, animal waste, sewage sludge, and municipal solid wastes (MSW), which collectively account for 57.39% of the total waste in the country. The objective is to explore their potential as energy sources.